Determination of the effective parameters of a triangular corrugated web for crane runway beams - Dias A. Okanov; Aleksandr A. Bryantsev; Mehmet B. Bozkurt; Sayat E. Niyetbay; Zhangazy N. Moldamuratov (Нанотехнологии в строительстве)
Introduction. The aim of this study is to investigate the performance of crane runway beams with triangular corrugated webs. These beams are increasingly popular in industrial construction because of to their enhanced shear resistance and structural efficiency. Flat webs have several disadvantages, including high stress levels and excessive material consumption. Optimizing the geometry of cor rugations makes it possible to improve strength and reduce the overall construction cost. Methods and Materials. The study is based on numerical modeling using the finite element method (FEM) in LIRA-CAD 2022 software and full-scale experimental testing. The performance of beams with both corrugated and flat webs was analyzed under wheel loads from cranes with lifting capacities of 10, 30, and 50 tons. Deformations and the distribution of normal and shear stresses were evaluated. Results and Discussion. The numeri cal model demonstrated high accuracy, with a maximum deviation of only 2.9% from experimental results. Crane runway beams with corrugated webs exhibited lower shear and normal stresses, reduced deflections, and more uniform force distribution. They also proved to be more economical due to lower material consumption and reduced labor intensity. Additionally, the corrugated beams showed enhanced economic performance, reducing material costs. Conclusion. Triangular corrugated web beams outperform traditional flat web beams in structural and economic terms. The findings support the use of optimized corrugation profiles to increase load-bearing capacity and reduce production costs. These results are relevant for optimizing crane beam design in industrial structures.